Wacky Wednesday - LeSieg, Theo., 1904-; Booth, George, 1926- ([New York] Beginner Books, 1974)
Drawings and verse point out the many things that are wrong one wacky Wednesday.
"59."
Keywords: Counting; Stories in rhyme